Analisis Gaya Hidup Sehat Siswa Kelas XII SMAN 14 Semarang di Era Pandemi Covid-19 - Fitrian Rama Aditya; Maftukin Hudah; Utvi Hinda Zhannisa (Journal of Physical Activity and Sports (JPAS), 2021)
The Covid 19 pandemic that occurred in Indonesia caused concern for students. Efforts that can be made to reduce the risk of contracting Covid 19 are adopting a healthy lifestyle. The purpose of this study was to determine the application of a healthy lifestyle for class XII students of SMA Negeri 14 Semarang in the era of the COVID-19 pandemic. This research uses qualitative research with a descriptive approach. The research subjects were students of class XII SMA Negeri 14 Semarang. Collecting data using interview, observation and documentation methods. Data analysis used methods carried out by data reduction, data presentation and drawing conclusions. The results of the study: 1) The use of masks has been applied well. 2) Maintaining cleanliness is carried out well in terms of efforts to maintain personal and environmental hygiene. 3) The implementation of keeping the distance has not been maximally seen from the students who are still clustered. 4) The level of awareness of students to consume balanced nutrition is good, but there are obstacles such as the income factor of parents. 5) The implementation of physical activity has been done by most of the students. 6) The implementation of adequate rest has not been done with less than optimal. 7) The smoking habit was only done by a few students. None of the students consumed alcoholic beverages. Based on the results of the study, it can be concluded that the application of a healthy lifestyle for class XII SMA Negeri 14 Semarang has been going quite well..   Keyword : Healthy Lifestyle, High School Students, Pandemic Covid-19 Abstrak Pandemi covid 19 yang terjadi di Indonesia menimbulkan kekhawatiran bagi siswa. Upaya yang dapat dilakukan untuk mengurangi risiko tertular covid 19 adalah menerapkan gaya hidup sehat. Tujuan dari penelitian ini adalah mengetahui penerapan gaya hidup sehat siswa kelas XII SMA Negeri 14 Semarang di era pandemi covid 19. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan deskriptif. Subjek penelitian yaitu siswa kelas XII SMA Negeri 14 Semarang. Pengumpulan data menggunakan metode wawancara, observasi dan dokumentasi. Analisis data menggunakan metode yang dilakukan dengan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian : 1) Penggunaan masker sudah diterapkan dengan baik. 2) Menjaga kebersihan terlaksana dengan baik dilihat dari upaya untuk menjaga kebersihan diri dan lingkungan. 3) Penerapan jaga jarak belum maksimal dilihat dari siswa yang masih berkerumun. 4) Tingkat kesadaran siswa untuk mengonsumsi gizi seimbang sudah baik, tetapi terdapat hambatan seperti faktor pendapatan orang tua. 5) Penerapan aktivitas fisik sudah dilakukan sebagian besar siswa. 6) Penerapan istirahat yang cukup belum dilakukan dengan kurang maksimal. 7) Kebiasaan merokok hanya dilakukan beberapa siswa. Tidak ada siswa yang mengonsumsi minuman beralkohol. Berdasarkan hasil penelitian dapat disimpulkkan bahwa penerapan gaya hidup sehat siswa kelas XII SMA Negeri 14 Semarang sudah berjalan dengan cukup baik.   Kata kunci: Gaya Hidup Sehat, Siswa SMA, Pandemi Covid-19